The effect of blood protein adsorption on cellular uptake of anatase TiO2 nanoparticles - Allouni ZE (Dove Medical Press, 2015)
Zouhir E Allouni,1 Nils R Gjerdet,1 Mihaela R Cimpan,1,* Paul J Høl2,3,* 1Faculty of Medicine and Dentistry, Department of Clinical Dentistry, Biomaterials, University of Bergen, Bergen, Norway; 2Faculty of Medicine and Dentistry, Department of Clinical Medicine, Biomaterials, University of Bergen, Bergen, Norway; 3Department of Orthopaedic Surgery, Haukeland University Hospital, Bergen, Norway *These authors contributed equally to this work Abstract: Protein adsorption onto nanoparticles (NPs) in biological fluids has emerged as an important factor when testing biological responses to NPs, as this may influence both uptake and subsequent toxicity. The aim of the present study was to quantify the adsorption of proteins onto TiO2 NPs and to test the influence on cellular uptake. The surface composition of the particles was characterized by thermal analysis and by X-ray photoelectron spectroscopy. The adsorption of three blood proteins, ie, human serum albumin (HSA), γ-globulins (Glbs), and fibrinogen (Fib), onto three types of anatase NPs of different sizes was quantified for each protein. The concentration of the adsorbed protein was measured by ultraviolet-visible spectrophotometry using the Bradford method. The degree of cellular uptake was quantified by inductivity coupled plasma mass spectroscopy, and visualized by an ultra-high resolution imaging system. The proteins were adsorbed onto all of the anatase NPs. The quantity adsorbed increased with time and was higher for the smaller particles. Fib and Glbs showed the highest affinity to TiO2 NPs, while the lowest was seen for HSA. The adsorption of proteins affected the surface charge and the hydrodynamic diameter of the NPs in cell culture medium. The degree of particle uptake was highest in protein-free medium and in the presence HSA, followed by culture medium supplemented with Glbs, and lowest in the presence of Fib. The results indicate that the uptake of anatase NPs by fibroblasts is influenced by the identity of the adsorbed protein. Keywords: nanoparticles, titanium dioxide, proteins, adsorption, cellular uptake